Brain Function and Upper Limb Deficit in Stroke With Motor Execution and Imagery: A Cross-Sectional Functional Magnetic Resonance Imaging Study - Ma, Zhen-Zhen; Wu, Jia-Jia; Hua, Xu-Yun; Zheng, Mou-Xiong; Xing, Xiang-Xin; Ma, Jie; Li, Si-Si; Shan, Chun-Lei; Xu, Jian-Guang (Frontiers in Neuroscience, 2022)
Background: Motor imagery training might be helpful in stroke rehabilitation. This study explored if a specific modulation of movement-related regions is related to motor imagery (MI) ability. Methods: Twenty-three subcortical stroke patients and twenty-one age-matched controls were recruited. They were subjectively screened using the Kinesthetic and Visual Imagery Questionnaire (KVIQ-20). Then they underwent functional magnetic resonance imaging while performing 3 repetitions of different motor tasks (motor execution, and motor imagery). Two separate runs were acquired (motor execution tasks (EM and rest) and motor imagery (MI and rest); a block design). For the different tasks, analyses of cerebral activation and the correlation of motor/imagery task-related activity and the scores of KVIQ were performed. Results: During UH active grasp movement, we observed decreased activations in the contralateral precentral gyrus (PreCG), contralateral postcentral gyrus (PoCG) (p < 0.05, FWE corrected) and a positive correlation with the ability of FMA-UE (PreCG: r = 0.46, P = 0.028; PoCG: r = 0.46, P = 0.028). During active grasp of the AH, decreased activation in the contralateral postcentral gyrus (PoCG) was observed. (p < 0.05, FWE corrected). Motor imagery of UH induced significant activations of the contralateral superior frontal gyrus (SFG), inferior frontal gyrus, opercular part (IFGoperc), and ipsilateral ACC, while deactivation in the ipsilateral supplementary motor area (SMA)(p < 0.05, alphaSim correction). Ipsilateral ACC showed a negative correlation to the ability of motor imagery (r = -0.49, P = 0.022). Also, we can note the significant activation of contra-lesional middle frontal gyrus (MFG) during motor imagery of AH. Conclusion: Our results proved the dominant effects of motor imagery dysfunction that exist in stroke during the processing of motor execution. For the motor execution task, the enhancement of contralateral PreCG and PoCG contributed to reversing the motor dysfunction, while for the motor imagery task, the inhibition of contralateral ACC can increase the impaired KVIQ ability. The bimodal balance recovery model can explain our results well. Recognizing neural mechanisms is critical to help us formulate precise strategies when intervening with electrical or magnetic stimulation. Keywords: motor imagery, motor execution, stroke, fMRI